Degradation of distillery spent wash using monopolar parallel and monopolar series electrocoagulation process - Pujari, Sukanya; Wagh, Manoj; Dare, Shila (Universitas Muhammadiyah Surakarta, 2021)
In waste treatment and water management issues, electrocoagulation (EC) is the most cost-effective and environmentally friendly option. In the study, EC treatment of distillery spent wash was carried out using new electrodes packed with aluminium foil scraps. These metal scraps were packed in a mesh to function as anode and cathode electrodes. Electrochemical treatment was carried out for 150 minutes, and samples were analysed regularly to determine the colour and chemical oxygen demand (COD). The impact of operating parameters such as pH, applied current, electrolysis time, agitation speed, and electrode distance on colour and COD removal was investigated. The EC processes were carried out in monopolar parallel (MP-P) and monopolar series (MP-S). The MP-S connection measured the potential difference between the amplified pair of electrodes, whereas the output signals in the MP-P connection were formed by several input electrodes, resulting in a high removal rate. The results indicated that the MP-P relationships enhance the COD removal rate by 4.16 to 8.06 %. An optimum chemical oxygen demand degradation is 77.29 % at pH 3, and decolourisation is 76.55 % at pH 8.3. TDS is reduced to a maximum of 58.32 %, while sulfate and chloride are reduced to 64.72 and 20.44 %, respectively.